2013
DOI: 10.1042/bj20130194
|View full text |Cite
|
Sign up to set email alerts
|

A GPI anchor explains the unique biological features of the common NKG2D-ligand allele MICA*008

Abstract: The human MICA (MHC I-related chain A) gene, encoding a ligand for the NKG2D (NKG2-D type II integral membrane protein) receptor, is highly polymorphic. A group of MICA alleles, named MICA 5.1 (prototype, MICA*008), produce a truncated protein due to a nucleotide insertion in the transmembrane domain. These alleles are very frequent in all of the human populations studied and they have different biological properties, compared with full-length alleles, e.g. recruitment into exosomes, which makes them very pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 35 publications
(38 reference statements)
3
89
0
2
Order By: Relevance
“…Our observations are in line with findings by Ashiru et al (31), who demonstrated that MICA*008 can be anchored to the plasma membrane via GPI and released in association with exosomes or secreted through a mechanism that is dependent on exocytosis. Thus, effective blockade of sMICA release and accumulation in patient sera might require different strategies, depending on the patient's MICA genotype.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our observations are in line with findings by Ashiru et al (31), who demonstrated that MICA*008 can be anchored to the plasma membrane via GPI and released in association with exosomes or secreted through a mechanism that is dependent on exocytosis. Thus, effective blockade of sMICA release and accumulation in patient sera might require different strategies, depending on the patient's MICA genotype.…”
Section: Discussionsupporting
confidence: 82%
“…The notion that different MIC alleles exhibit distinct molecular structures and different shedding modalities (14,31) prompted us to examine whether the chemotherapeutic agents could differentially affect the release of distinct MICA alleles. To this end, the MM cell line LP1, which does not express endogenous MICA and MICB, was stably transduced with cDNA encoding MICA*008 (carrying a truncated cytoplasmic tail and released by exosomes or through exocytosis), MICA*019 (which represents the prototype of the long form of MICA alleles), or MICB and exposed to DOX treatment.…”
Section: Drug Treatment Of MM Cells Selectively Affects the Release Omentioning
confidence: 99%
“…EVs can provide a suitable membrane scaffold for membrane-bound proteins to exhibit their proper activity and membrane distribution. Bioactive membrane proteins can be naturally located to and expressed on EV surfaces [51], and membrane-associated proteins known to cluster into microdomains, such as GPI-anchored proteins, are selectively sorted in EV membranes [62,115117]. Thus, it is expected that the biological activity of membrane (-associated) proteins will be maximized in the membrane environment offered by EVs.…”
Section: Therapeutic Applications Of Surface-modified Evsmentioning
confidence: 99%
“…First, MICA*A5.1 is a truncated protein because a single nucleotide insertion in exon 5 leads to the appearance of a premature stop codon. It does not have a cytoplasmic tail and can be found in human cells in two forms: a surface protein attached to the membrane by glycosylphosphatidylinositol (GPI) anchor or soluble forms in intracellular compartments [17]. Secondly, MICA*A5.1 is located aberrantly on the apical surface of intestinal epithelial cells, instead of the basolateral surface where the interaction with intraepithelial T lymphocytes and NK cells takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the allele MICA*A5.1 consists of five GCT repetitions plus a guanine insertion in the second triplet [12], leading to the appearance of a premature stop codon and the expression of a truncated protein. MICA*A5.1 differs from the other MICA proteins in several aspects, as the cell location or the attachment to membrane [9,16,17]. A crystal structure of extracellular domains of MICA from the Protein Data Bank [18] and a diagram of the transmembrane region can be seen in Fig.…”
Section: Introductionmentioning
confidence: 99%